High resolution osmium data record three distinct pulses of magmatic activity during cretaceous Oceanic Anoxic Event 2 (OAE-2). (15th September 2020) - Sullivan, Daniel L.; Brandon, Alan D.; Eldrett, James; Bergman, Steven C.; Wright, Shawn; Minisini, Daniel
Abstract: Oceanic Anoxic Event 2 (OAE-2) occurred at the Cenomanian-Turonian boundary (∼94.1 Ma) and was a time of profound global changes in ocean chemistry and the carbon cycle. This event was characterized by a positive carbon isotope excursion (CIE) caused by massive organic carbon burial, global greenhouse temperatures, ocean deoxygenation, and changes in ocean life driven by large igneous province (LIP) activity. LIPs throughout the Phanerozoic have had dynamic magma flux, with episodes of major eruptions interspersed with periods of relatively less intense eruptions. A possible trigger for LIP activity throughout the Phanerozoic has been attributed to extraterrestrial impacts because there are multiple contemporaneous occurrences of large craters, LIP activity, and mass extinctions in the geologic record. At the Cenomanian-Turonian boundary, there is a 25 km diameter (rim-to-rim) complex crater in NW Alberta, Canada known as the Steen River impact structure dated at 91 ± 7 Ma (Carrigy and Short, 1968). An alternative explanation for those craters found contemporaneous with LIP activity and mass extinctions is that they were created by large explosive events related to LIP activity. Explosive events associated with mantle plume incubation beneath cratonic lithosphere have been suggested to create geologic features commonly attributed to impacts (e.g., shocked quartz, microspherules, etc.). Currently, the trigger for LIP activity during OAE-2, as well as the duration of LIP activity and the temporal variation and magnitude of eruption rates are not well constrained. To address the issue of LIP eruption rates and the trigger for LIP activity, we examined osmium (Os) abundances and isotopes as well as highly siderophile element (HSE; for this study: Re, Ru, Pd, Os, Ir, Pt) abundance data from a continuous sedimentary section spanning OAE-2. The section is from the Eagle Ford Group in the Iona-1 core, deposited in the Cretaceous Western Interior Seaway (KWIS). We found three high Os concentration intervals with mantle-like initial Osi isotope (initial 187 Os/ 188 Os) values of ∼0.16. These intervals are interpreted to reflect high-flux LIP magmatic pulses. Between the pulses, lower Os abundances with more radiogenic Osi values of ∼0.20 are observed, which we interpret as low-flux LIP activity between the high-flux periods. This trend of high-and-low flux Os concentration pulses with mantle-like Osi values during the high flux periods is found in another KWIS core (USGS Portland #1) deposited to the north of Iona-1, and in core Deep Sea Drilling Project (DSDP) Site 530 Hole A (hereafter DSDP 530A; drilled off-shore Namibia in the Angola Basin) deposited in the Southern Hemisphere. Before and throughout the Iona-1 core OAE-2 interval, HSE abundance patterns indicate a mantle source for the unradiogenic Os, and are not consistent with an extraterrestrial impact trigger or contribution to LIP activity during OAE-2. This evidence for multiple high-flux pulses of LIP activity driving ocean deoxygenation has implications for the modern ocean, which is currently experiencing deoxygenation. These results provide new constraints on subsequent high-flux periods that extended the event. The first high-flux period started ∼60 Kyr after our selection of the onset of the CIE. The second and third high-flux periods started ∼270 and ∼400 Kyr after the onset of the CIE, respectively. After the third high-flux period, δ 13 Corg and Os isotope ratios shifted back to pre-excursion values over ∼585 kyr. In the Iona-1 core, OAE-2 lasted for 1.04 ± 0.12 Myr based on our selection of the CIE.